Quantitative analysis of social and financial market development - Barnett, William A.; Sergi, Bruno S. (International symposia in economic theory and econometrics ;, 2022)
This 30th volume of the International Symposia in Economic Theory and Econometrics explores the latest social and financial developments across Asian markets. Chapters cover a range of topics such as the impact of COVID-19 related events in Southeast Asia along the determinants of capital structure before and during the pandemic; the influence of new distribution concepts on macro and micro economic levels; as well as the effects of long-term cross-currency basis swaps on government bonds. These peer-reviewed papers touch on a variety of timely, interdisciplinary subjects such as real earnings impact and the effects of public policy. Together, Quantitative Analysis of Social and Financial Market Development is a crucial resource of current, cutting-edge research for any scholar of international finance and economics.